1995
DOI: 10.1073/pnas.92.10.4299
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid P component prevents proteolysis of the amyloid fibrils of Alzheimer disease and systemic amyloidosis.

Abstract: Extracellular deposition of amyloid fibrils is responsible for the pathology in the systemic amyloidoses and probably also in Alzheimer disease [Haass, C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
243
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(251 citation statements)
references
References 40 publications
5
243
0
3
Order By: Relevance
“…Neither were these proto®brils resistant to trypsin treatment in the presence of the protease resistant SAP, in agreement with our EM results that showed no binding of SAP to these structures. Therefore, SAP is seemingly not necessary for the initiation of amyloid ®brillogenesis, but may stabilize and protect mature ®brils [15]. The ®nding that development of amyloidosis in SAP-de®cient mice was delayed compared to in normal mice [16,17] is compatible with the interpretation of our data.…”
Section: Discussionsupporting
confidence: 88%
“…Neither were these proto®brils resistant to trypsin treatment in the presence of the protease resistant SAP, in agreement with our EM results that showed no binding of SAP to these structures. Therefore, SAP is seemingly not necessary for the initiation of amyloid ®brillogenesis, but may stabilize and protect mature ®brils [15]. The ®nding that development of amyloidosis in SAP-de®cient mice was delayed compared to in normal mice [16,17] is compatible with the interpretation of our data.…”
Section: Discussionsupporting
confidence: 88%
“…87 Furthermore, it has been shown that SAP inhibits the degradation of several types of amyloid fibrils by proteases. Tennent et al 88 suggested that SAP protects amyloid from proteolytic degradation in vivo by binding to fibrils and masking fibrillar conformation.…”
Section: Serum Amyloid P Componentmentioning
confidence: 99%
“…98 Similarly, the calcium-dependent binding of SAP to amyloid fibrils formed from A, serum amyloid A protein or immunoglobulin light chain, protected the fibrils from subsequent proteasemediated degradation. 88 This in turn led to suggestions that SAP may promote the persistence of amyloid deposits in vivo. For some protein substrates, at low clusterin:substrate ratios (1:50-1:500), clusterin promoted the formation of aggregates with an increased level of thioflavin T fluorescence, suggesting that (at these ratios) it promoted the formation of fibrils from calcitonin, -synuclein and A.…”
Section: Effects Of Ecs On Amyloid Formation In Vitromentioning
confidence: 99%
“…Control fibrils were isolated from the amyloidotic spleen of a wild hare (Lepus europaeus) [20]. All preparations displayed characteristic red-green dichroism in cross-polarized light microscopy (DMR XA2-QWIN; Leica Microsystems, Milton Keynes, UK) after staining with alkaline alcoholic Congo red [21,22], a fibrillar ultrastructure by negative stain transmission electron microscopy [23] and specific binding by serum amyloid P component [24,25]; their purity and protein content were analysed by reduced SDS-PAGE (ExcelGels; GE Healthcare, Chalfont St. Giles, UK) [16].…”
Section: Amyloid Fibrilsmentioning
confidence: 99%